2019
DOI: 10.1136/bmjopen-2019-032738
|View full text |Cite
|
Sign up to set email alerts
|

Using theatre as an arts-based knowledge translation strategy for health-related information: a scoping review protocol

Abstract: IntroductionSubstantial delays in translating evidence to practice mean that many beneficial and vital advances in medical care are not being used in a timely manner. Traditional knowledge translation (KT) strategies have tended to target academics by disseminating findings in academic journals and at scientific conferences. Alternative strategies, such as theatre-based KT, appear to be effective at targeting broader audiences. The purpose of this scoping review is to collate and understand the current state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… 33 This scoping review protocol is inspired by and based on previous scoping reviews on similar KT activities and tools. 34 35 …”
Section: Methods and Analysismentioning
confidence: 99%
“… 33 This scoping review protocol is inspired by and based on previous scoping reviews on similar KT activities and tools. 34 35 …”
Section: Methods and Analysismentioning
confidence: 99%
“…There is a compelling rationale for arts-based knowledge translation in health and that is the gap between research and clinical practice (Hall et al, 2019). Dew and Boydell (2017) estimate that it takes 17 years for health research to reach practice settings and even then, only 14% of all health research influences clinical practice from day-to-day.…”
Section: Arts-based Knowledge Translation In Healthmentioning
confidence: 99%
“…Arts-based knowledge translation in health takes a variety of forms including theatre (Hall et al, 2019), photovoice (MacDonald et al, 2020), body mapping (Boydell, 2021), dance (Boydell, 2011) and poetry (Lapum et al, 2012). While tensions inevitably exist between art and scientific evidence, many arts-based researchers in health see their translation work as contextualising objective knowledge-that is, placing scientifically generated knowledge into a social, sensorial and/or embodied form (Rieger & Schultz, 2014).…”
Section: Arts-based Knowledge Translation In Healthmentioning
confidence: 99%
“…[13] It has been well developed in the literature that ABKT can evoke affective responses, construct alternative forms of representation that promote dialogue, shared storytelling, and reflection, and engage audiences on emotive, embodied, and intellectual levels. [15] Research has shown that creative knowledge translation through the use of dementia simulations has proven to be successful in improving content retention and empathy in nursing students, making it a key area to focus on and refine. [12] Virtual reality is an emerging technology that is being adapted to several uses.…”
Section: Literature Reviewmentioning
confidence: 99%